DEVELOPMENT OF EST-SSR MARKERS TO ASSESS GENETIC DIVERSITY OF BROCCOLI AND ITS RELATED SPECIES - Nur Kholilatul Izzah; Reflinur Reflinur; Tae-Jin Yang (Indonesian Agency for Agricultural Research and Development, 2016)
Development of Expressed Sequence Tag-Simple Sequence Repeat (EST-SSR) markers derived from public database is known to be more efficient, faster and low cost. The objective of this study was to generate a new set of EST-SSR markers for broccoli and its related species and their usefulness for assessing their genetic diversity. A total of 202 Brassica oleracea ESTs were retrieved from NCBI and then assembled into 172 unigenes by means of CAP3 program. Identification of SSRs was carried out using web-based tool, RepeatMasker software. Afterwards, EST-SSR markers were developed using Primer3 program. Among the identified SSRs, trinucleotide repeats were the most common repeat types, which accounted for about 50%. A total of eight primer pairs were successfully designed and yielded amplification products. Among them, five markers were polymorphic and displayed a total of 30 alleles with an average number of six alleles per locus. The polymorphic markers were subsequently used for analyzing genetic diversity of 36 B. oleracea cultivars including 22 broccoli, five cauliflower and nine kohlrabi cultivars based on genetic similarity matrix as implemented in NTSYS program. At similarity coefficient of 61%, a UPGMA clustering dendrogram effectively separated 36 genotypes into three main groups, where 30 out of 36 genotypes were clearly discriminated. The result obtained in the present study would help breeders in selecting parental lines for crossing. Moreover, the novel EST-SSR markers developed in the study could be a valuable tool for differentiating cultivars of broccoli and related species.